Ruta Turística “Pucará – El Tambo – La Era” de la Parroquia El Tambo, Cantón Catamayo, Provincia de Loja - Martínez Armijos, Sayra Paola (2018)
Tourism focuses on providing sustainable development to the communities that decide to apply it, this development is part of the economic and social growth of the community, thus achieving a better quality of life. The World Tourism Organization proposes the conversion of tourism in an activity that has as its main objective the economic, social and environmental balance and with the generation of jobs, improvement of the tourist infrastructure, incorporation of basic services and without neglecting the environmental part of the tourist attractions this purpose can be achieved. El Tambo is a rural parish of the canton Catamayo, located just 20 minutes from the center of this city; its dry subtropical climate, its beautiful landscapes, variety of flora and fauna, its large hydrography network and above all the customs and traditions of its people make this place suitable to be visited. For these reasons the present research work was proposed, which had as its general objective, Propose the tourist route: "Pucará - El Tambo - La Era" of the parish El Tambo, canton Catamayo, province of Loja; managing to contribute significantly to the tourist development of the area. In the same way, the following specific objectives were proposed: Carry out the tourist diagnosis of the El Tambo parish; Design the tourist route "Pucará - El Tambo - La Era" of the canton Catamayo and carry out the socialization of the proposal of the tourist route to the parish authorities. For the elaboration of the objectives, it is used in different methods and techniques; in the first specific objective the analytical and inductive method was used; with the help of direct observation techniques and interviews, information on tourist attractions was obtained through the inventory tabs of the Ministry of Tourism (MINTUR), as well as identifying 6 strengths, opportunities, weaknesses and threats through of the SWOT matrix. For the elaboration of the second objective, the synthetic and deductive methods were used; the GPS was used to lift coordinates, altitude, travel time and distances; camera for digital support and a matrix prepared by the Ministry of Tourism of Ecuador to validate routes, in which the necessary components of the same are established. A map of the Tourist Route was drawn up, using pictograms of natural tourist attractions, tourist activities, support services and restriction pictograms. The logo was also designed and the name of the route called "El Tambo Waterfalls Route" was established. Therefore, the promotion and diffusion strategies of the route were established in order to provide the tourist facilities for the research topic; a script and itinerary of the tourist route was designed following the order established in it. The results of the research were socialized through the technique of Rapid Analysis and Participatory Planning (MARPP), which was used to develop the participatory workshop and the deductive method, which allowed the community in general to participate in the socialization of the route proposal, contributing with suggestions, conclusions and recommendations of the socialized theme. Also as a recommendation to the work done, it was said to take into account tourist attractions that begin to be known in the parish as is the case of the Pata del Diablo waterfall in the Chapamarca sector; also take into consideration that for the proposed tourist route you can use rancheras as a means of transport, since these can be equipped to transport tourists to the waterfalls. Finally as results it was determined that the "El Tambo waterfalls route" will contribute to the touristic development of the parish, since the most important natural and cultural tourist attractions are immersed in it. 7 As conclusions and recommendations of the thesis work, where they indicate the importance of executing this type of projects providing a great contribution for the tourist improvement of the parish. As conclusions, it was established that through the tourist diagnosis, El Tambo parish has natural and cultural tourist attractions of great importance; It is also concluded that the design of the tourist route proposed in the present work will help to adapt, maintain and disseminate the tourist attractions. In this way, the parish GAD was recommended to elaborate tourism projects aimed at the diffusion and economic growth of the parish, to take the necessary steps to adapt all the tourist attractions, which would facilitate the arrival of tourists and also improve the quality of life of their families population. It is also recommended to the National University of Loja, specifically to the career of Tourist Administration, so that through the students conduct guidance practices, thus generating support for the parish. To the Ministry of Tourism, to provide training in tourism to tourism service providers and collectivity in general who wish to be linked to this activity, so that the community is the one who receives the corresponding remuneration for their services rendered.